Poverty and Social Impact in the Agricultural Sector: Lessons from Experience - Alwang, Jeffrey (2012)
This article draws on the donor experience in agriculture-sector reforms to analyse the contribution of Poverty and Social Impact Analysis (PSIA) to improved rural policy. A decision-theoretic framework is presented showing that effective PSIAs should target reforms where institutional distortions and uncertainty about key policy parameters are greatest. The framework is applied to nine cases of World Bank-sponsored PSIAs, and results show that, while they have generally been effective, their impacts can be improved by identifying key uncertainties a priori, better identifying and engaging stakeholders, and improving the integration of quantitative and qualitative components.